Transformasi Pendidikan Islam dalam Mendorong Self-Regulated Learning Siswa Madrasah: Studi Empiris di MTs Mumtaz Palangka Raya - Winda, Winda; Surawan, Surawan (Lembaga Yasin AlSys, 2025)
Most students struggle with independent learning due to low motivation, which typically arises only when completing homework or preparing for exams. This issue is closely related to the concept of self-regulated learning (SRL). This study aims to explore how Islamic education at MTs Mumtaz fosters the development of SRL among students. A qualitative approach was employed, with 16 eighth-grade students as research subjects. Data were collected through structured interviews, direct observation, and documentation. Data analysis followed four stages: data collection, data reduction, data presentation, and conclusion drawing or verification. The findings reveal that Islamic education at MTs Mumtaz Palangka Raya effectively promotes SRL through the internalization of Islamic values, which serve as the foundation for self-regulation. These values include sincerity (ikhlas), discipline, and responsibility. The internalization process strengthens students’ awareness and independence in managing their learning actively and continuously. These findings align with the theory of Islamic value-based education as a foundation for the development of self-regulation in learners. This study offers important insights for schools in designing value-based learning strategies that support SRL and opens opportunities for further research on the role of Islamic values in promoting autonomous learning.